More than just exosomes: distinct Leishmania infantum extracellular products potentiate the establishment of infection - Perez-Cabezas, B (2019)
The use of secretion pathways for effector molecule delivery by microorganisms is a trademark of pathogenesis. Leishmania extracellular vesicles (EVs) were shown to have significant immunomodulatory potential. Still, they will act in conjunction with other released parasite-derived products that might modify the EVs effects. Notwithstanding, the immunomodulatory properties of these non-vesicular components and their influence in the infectious process remains unknown. To address this, we explored both in vitro and in vivo the immunomodulatory potential of promastigotes extracellular material (EXO), obtained as a whole or separated in two different fractions: EVs or vesicle depleted EXO (VDE). Using an air pouch model, we observed that EVs and VDE induced a dose-dependent cell recruitment profile different from the one obtained with parasites, attracting significantly fewer neutrophils and more dendritic cells (DCs). Additionally, when we co-inoculated parasites with extracellular products a drop in cell recruitment was observed. Moreover, in vitro, while VDE (but not EVs) downregulated the expression of DCs and macrophages activation markers, both products were able to diminish the responsiveness of these cells to LPS. Finally, the presence of Leishmania infantum extracellular products in the inoculum promoted a dose-dependent infection potentiation in vivo, highlighting their relevance for the infectious process. In conclusion, our data demonstrate that EVs are not the only relevant players among the parasite exogenous products. This, together with the dose-dependency observed, opens new avenues to the comprehension of Leishmania infectious process. The approach presented here should be exploited to revisit existing data and considered for future studies in other infection models.